2011
DOI: 10.1016/j.ejcts.2010.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive repair after inefficient open surgery for pectus excavatum☆

Abstract: Minimally invasive repair is a safe and easy operation for the correction of pectus excavatum. Previous open surgical repair is not a contraindication for the redo minimally invasive surgery, and it can be performed with acceptable morbidity and length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…There are also various reports demonstrating the safety of MIRPE after open repair of PE, which is affirmed by our clinic's experience as well [8].…”
Section: Commentsupporting
confidence: 61%
“…There are also various reports demonstrating the safety of MIRPE after open repair of PE, which is affirmed by our clinic's experience as well [8].…”
Section: Commentsupporting
confidence: 61%
“…Regarding postoperative complication risk, outcomes described in the literature are mixed and our results were not always concordant. Some studies reported a slight increased rate of early complications such as pleural effusion requiring drainage (6%), hemothorax (8%), pericarditis (4%), and increased rate of pulmonary parenchymal laceration and myocardial injuries [5,29] while other investigators report no increase in the rate of complications [4]. In addition patients who had a previous Ravitch operation, when managed with Nuss revision, appear to have an increased rate (12%) of bar displacement [6,16].…”
Section: Characteristicsmentioning
confidence: 90%
“…Bu olgularda retrosternal yapışıklıklar konusunda dikkatli olunmalı, torakoskopun gözetiminde tünel oluşturulurken titiz çalışılmalı, gereken olgularda toraks dreni yerleştir-mekten kaçınılmamalıdır (10,19,33,34).…”
Section: Nüks Ve Reoperasyonunclassified